High risk cases in obstetrics - Daflapurkar, Shruti Bangale (Jaypee Brothers Medical Publishers (P) Ltd, 2014)
Comprehensive guide to high risk cases in obstetrics covering numerous common and more complicated disorders. Extensive references for further reading